2005
DOI: 10.1088/0953-8984/17/11/023
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in simple elemental solids—a computational study of boron-doped diamond and high pressure phases of Li and Si

Abstract: The superconducting phase of several elemental solids under ambient (p-doped diamond) and high pressure conditions (face-centred cubic phases of Li and Si–V) have been studied with the linear response method. The computed superconducting temperatures, based on the weak coupling Bardeen–Cooper–Schrieffer theory, are found to be in good agreement with experiments. Analysis of the electronic structure and phonon band structures shows that changes in the chemical bonding are responsible for the strong electron–pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 29 publications
5
28
0
Order By: Relevance
“…In this context it is interesting to point out that recent theoretical studies of fcc Li [27,28] and sh Si [29] have shown that phonon softening of TA modes contributes significantly to electronphonon coupling resulting in relatively high critical temperatures in these materials. Since the electronphonon parameter 2 F ( )/ N E λ ν µ · Ò, electron-phonon coupling is expected to increase with increasing pressure, which in the case of Sb-I is in accordance with the results obtained from the analysis of the line-width data.…”
Section: Discussionmentioning
confidence: 99%
“…In this context it is interesting to point out that recent theoretical studies of fcc Li [27,28] and sh Si [29] have shown that phonon softening of TA modes contributes significantly to electronphonon coupling resulting in relatively high critical temperatures in these materials. Since the electronphonon parameter 2 F ( )/ N E λ ν µ · Ò, electron-phonon coupling is expected to increase with increasing pressure, which in the case of Sb-I is in accordance with the results obtained from the analysis of the line-width data.…”
Section: Discussionmentioning
confidence: 99%
“…15 There have been extensive theoretical studies of superconductivity in the fcc phase of Li under pressure. 26,[28][29][30][31][32][33][34][35][36][37] In particular, it has been suggested that superconductivity in fcc Li is driven by Fermi-surface nesting 30,31 and Kohn anomalies, 30 resulting in an unusually high T c . On the other hand, no theoretical investigation has been made on superconductivity of the high-pressure cI16 phase based on firstprinciples calculation of the phonon spectra and the electronphonon spectral function.…”
Section: B High Pressure Fcc\ Ci16 Transitionmentioning
confidence: 99%
“…Theoretical works on pressure-induced superconductivity so far, however, have focused on the fcc phase only. [26][27][28][29][30][31][32][33][34][35][36][37] The only exception is the study on fcc and cI16 by Christensen and Novikov 26 based on a rigid muffintin approximation-which proved to be inadequate for Li ͑Ref. 34͒-and without calculation of the phonon spectra for cI16.…”
Section: Introductionmentioning
confidence: 99%
“…by using the density-functional perturbation theory (DFPT). 4) The applications of DFPT in high-temperature element superconductors 5,6) suggest that the technique enables us to obtain a reasonable estimation of the transition temperature T c when the essential pairing mechanism is the electron-phonon-interaction-mediated stabilization of superconductivity. The method may also predict how to enhance the T c of compound superconductors.…”
Section: Introductionmentioning
confidence: 99%